The Relation Between Breast Care And The Incidence Of Breast Milk Dams (Engorgement) In Postpartum Mothers - Titin Novayanti Dey; Nurviza Arianti Azma; Dwi Handayani; Siti Sarah Bintang (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2023)
Breastfeeding is a natural event that occurs after childbirth for a woman which is beneficial for both mother and baby. Breastfeeding problems that can occur during the puerperium or lactation are breast engorgement or also called breast milk dams. Breast milk dams occur due to superior lactiferous ducts or glands that are not emptied completely, lack of information and services provided regarding breast care. Based on the 2017 Indonesian Demographic and Health Survey (IDHS) data, it was stated that there were 77,231 postpartum mothers who experienced breastfeeding dams or (37.12%) postpartum mothers. The purpose of this study was to determine the relationship between breast care and the incidence of breastfeeding dams in postpartum mothers at the Pratama Nining Pelawati Clinic, Kec. Lubuk Pakam Kab. Deli Serdang in 2022. Research Methods The type of research used is descriptive analytical using the Cross Sectional method, which is a method of collecting data at the same time. The population of this study found 41 postpartum mothers. The sample in this questionnaire was collected by 37 postpartum mothers using the purposive technique. Data analysis using Chi-Square test. The results of the study of 37 respondents, most of whom had poor breast care were 26 people (70.3%) postpartum mothers, the majority of postpartum mothers who experienced breastfeeding were 24 people (64.9%). There is a relationship between breast care and the incidence of breast milk engorgement for postpartum mothers, obtained p-value 0.003 <0.05. Postpartum mothers already know about information about breast care, it is hoped that postpartum mothers will also be more diligent in carrying out breast care after giving birth and postpartum mothers will add more insight and knowledge about breast care to prevent breast milk damming.